Feasibility of enzalutamide on patients with recurrent non-muscle-invasive bladder cancer with marker tumors: phase I study - Takashi Kawahara; Shuya Kandori; Takahiro Kojima; Bryan J. Mathis; Masanobu Shiga; Hiroyuki Nishiyama (BMC Research Notes)
Abstract Objective Recent preclinical and retrospective clinical evidence shows that androgen receptor (AR)-mediated signals have significant roles in development of non-muscle invasive bladder cancer (NMIBC). Here, we conducted a single-center, phase I study to assess the feasibility and efficacy of enzalutamide in patients having recurrent NMIBC with marker tumors. Patients with NMIBC who cannot achieve complete transurethral resection (TUR) or with recurrence within a year after the TUR, were enrolled. The patients were administered oral enzalutamide at 160 mg dose, once daily for four weeks. Clinical response at the end of the treatment was evaluated using cystoscopy. Results Of the six patients enrolled, two experienced multiple recurrences. All the patients received the planned administration of enzalutamide. Enzalutamide was tolerable and all patients were able to complete the planed treatment, although four patients experienced mild treatment-related adverse events (AEs), but AEs with grade 2 or more were not observed. As for efficacy, three patients showed no change while the remaining three showed disease progression. Immunohistochemical analysis did not showed the strong staining of AR in the latest tumors. This is the first clinical study on enzalutamide treatment for NMIBC patients. In this study, four weeks of enzalutamide administration was well tolerated, however showed no clinical response for non-strong staining of AR. Trial registration: University Hospital Medical Information Network UMIN000026520 (date registration: 2017/3/13).